2013
DOI: 10.1103/physrevlett.111.088301
|View full text |Cite
|
Sign up to set email alerts
|

Complex Tracer Diffusion Dynamics in Polymer Solutions

Abstract: We employ fluorescence correlation spectroscopy (FCS) and coarse-grained molecular dynamics simulations to study the mobility of tracers in polymer solutions. Excluded volume interactions result in crowding-induced slowdown, depending only on the polymer concentration. With specific tracer-polymer attractions, the tracer is slowed down at much lower concentrations, and a second diffusion component appears that is sensitive to the polymer chain length. The two components can be resolved by FCS, only if the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 33 publications
5
61
0
Order By: Relevance
“…Careful analysis of the ACFs (as described in our previous work on this system 16 ) showed that the existence of a prolonged interaction between the streptavidin and the dextran can be ruled out. Indeed, if tracer/polymer complexes are stable enough to diffuse through the observation volume without dissociating, a second separate diffusion term should appear in the ACF, as indeed observed in systems where specific interactions exist between the tracer and the polymer 103 . No such term is observed in the case of streptavidin and dextran.…”
Section: The Anomalous Yet Brownian Motion Of Proteins In Crowded Dementioning
confidence: 99%
See 1 more Smart Citation
“…Careful analysis of the ACFs (as described in our previous work on this system 16 ) showed that the existence of a prolonged interaction between the streptavidin and the dextran can be ruled out. Indeed, if tracer/polymer complexes are stable enough to diffuse through the observation volume without dissociating, a second separate diffusion term should appear in the ACF, as indeed observed in systems where specific interactions exist between the tracer and the polymer 103 . No such term is observed in the case of streptavidin and dextran.…”
Section: The Anomalous Yet Brownian Motion Of Proteins In Crowded Dementioning
confidence: 99%
“…This does not immediately exclude, however, a more dynamic interaction scenario, where tracer molecules may bind and unbind during their passage through the detection volume. The duration of the tracer/polymer interaction would then introduce a characteristic timescale in the system, which, if similar to the characteristic residence time of the tracer in the FCS observation volume, might produce a deformation of individual ACFs undistinguishable from that caused by FBM 103 . An analytical form for the ACF can be derived in the case of rapid binding and unbinding to a single type of immobile "traps" ("stickand-diffuse" model, used to explain the mobility of synaptic vesicles 34 and transcription factors 104 ).…”
Section: The Anomalous Yet Brownian Motion Of Proteins In Crowded Dementioning
confidence: 99%
“…We used a terylenediimide derivative (TDI) as fluorescent tracer, which is well soluble in the used organic solvents. All autocorrelation curves recorded in both gel systems (Figure S8a,b, Supporting Information) could be adequately fitted by an analytical model equation, suggesting single component Fickian diffusion (no specific interactions between TDI tracers and the gels) . In the gels, the tracer diffusion rates (represented by their diffusion coefficient D ; see the Supporting Information for details) decrease as a consequence of the confinement effect of the polymer network.…”
Section: Resultsmentioning
confidence: 78%
“…Ultimately, the issue with the diffusion law is that it collapses the rich information contained in the shape of the ACF into a single value, τ 1/2 . In contrast, analysis of the detailed shape of the ACFs obtained at different w can give a lot of information about the underlying process (as shown for obstructed diffusion (22), two-component diffusion (38,39) or diffusion in phase separated membranes (50)). However, it is model-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…We then considered the general case, where particles can switch back and forth between two simple diffusion modes with Poisson statistics (k on = k off = 500 s −1 ). In this scenario (one of the few considered before in the context of VLS-FCS (38,39)), we expect a cross-over around the relaxation time, τ c = 1/(k on + k off ). In the "fast diffusion" regime (τ τ c ) tracers remains in the same state while crossing the observation volume and behave as two separate populations.…”
Section: Two-component Diffusionmentioning
confidence: 93%